Exploring the Potential of Lifestyle and Dietary Intervention to Improve In Vitro Fertilization Outcomes in Overweight and Obese Women: Systematic Review and Meta-Analysis - Abdullah, Muhammad Raoul Taufiq; Hestiantoro, Andon (UIMA Press, 2025)
Lifestyle and dietary interventions have been proposed to improve in vitro fertilization (IVF) outcomes in women with overweight and obesity, conditions known to reduce reproductive success. This systematic review followed PRISMA guidelines and searched PubMed, MEDLINE, and Scopus up to July 2025. Four randomized controlled trials involving 433 participants met inclusion criteria. A fixed-effects meta-analysis showed that weight loss interventions significantly increased clinical pregnancy rates (OR 1.55; 95% CI 1.03–2.35; p=0.04), with low heterogeneity (I²=32%). The strongest effect was reported in Sim 2014 (OR 5.07; 95% CI 1.21–21.28). Improvement in IVF outcomes is likely mediated through enhanced insulin sensitivity, reduced inflammation, and better hormonal regulation. Although both obesity and advanced maternal age reduce fertility, obesity has a greater impact on IVF success in younger women; therefore, weight reduction may be particularly beneficial for women under 35–38 years. In contrast, delaying treatment for weight loss may disadvantage older women due to age-related fertility decline. Overall, lifestyle-based weight loss significantly improves IVF outcomes and should be integrated into treatment planning for overweight and obese patients.